Output of occurrence data on brachiopod genera of a query to the Paleobiology Database on December 3rd, 2016 - Paleobiology Database (Supplement to: Boyle, James (2017): Quantifying geographic range measures and their utility as extinction risk proxies. PeerJ, 5, e3379v1, https://doi.org/10.7287/peerj.preprints.3379v1, 2017)
Geographic range is used as a correlate of extinction risk for extant and extinct organisms across the fields of conservation and paleobiology. However, the exact method used to measure geographic range, the biases, and the limitations of each are rarely discussed explicitly despite their potential to impact conclusions. Here I examine and quantify properties of five commonly used measures of geographic range (convex hull area, maximum pairwise great circle distance, latitudinal range, longitudinal range, and cell count) along with a rarely used measure (minimum spanning tree distance) in the context of three datasets. A simulated dataset of two shapes with known areal limits, a paleontological occurrence dataset of pre-Cenozoic brachiopod genera from the Paleobiology Database (PBDB), and 50000 occurrence records of birds species in the western hemisphere from the eBird database.